REGULACIÓN DE PHYTOLIRIOMYZA JACARANDAE (DIPTERA: AGROMYZIDAE) POR PARASITOIDES (HYMENOPTERA: CHALCIDOIDEA) EN CÓRDOBA, ARGENTINA - Salvo, Adriana; Valladares, Graciela (Acta Entomológica Chilena, 2022)
A population of Phytoliriomyza jacarandae Steyskal & Spencer (Díptera: Agromyzidae) was sampled monthly from April 1991 through July 1994 in order to study the temporal variations in host and parasitoid populations. Adults were reared, identified and counted, which allowed characterization of the parasitoid complex and quantification of the parasitism. Ten parasitoid species were recorded, two of them mentioned for the first time parasitizing P. jacarandae. Chrysonotomyia thysanoides (De Santis) and Diglyphus websteri (Crawford) were the dominant species. Parasitism rates of D. websteri were related to host density on the previous sampling date. An effective host regulation by parasitoids is suggested by a negative relationship between host density and percentage parasitism on previous sampling date.